2019
DOI: 10.3390/ijms20040998
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Promotes Mitochondrial Biogenesis and Protects against Seizure-Induced Neuronal Cell Damage in the Hippocampus Following Status Epilepticus by Activation of the PGC-1α Signaling Pathway

Abstract: Peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) is known to regulate mitochondrial biogenesis. Resveratrol is present in a variety of plants, including the skin of grapes, blueberries, raspberries, mulberries, and peanuts. It has been shown to offer protective effects against a number of cardiovascular and neurodegenerative diseases, stroke, and epilepsy. This study examined the neuroprotective effect of resveratrol on mitochondrial biogenesis in the hippocampus following experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 56 publications
(130 reference statements)
5
60
0
Order By: Relevance
“…In a previous report [ 26 ], we demonstrated that resveratrol is a PGC-1α activator, and it can activate PGC-1α and the following signaling pathways and then promote mitochondrial biogenesis. To determine the causality of PGC-1α in modulation of VEGF on this experimental paradigm, we tested the effects of resveratrol, as a positive control, and siRNA against pgc-1α, as a negative control, on VEGF expression in the hippocampus following status epilepticus.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…In a previous report [ 26 ], we demonstrated that resveratrol is a PGC-1α activator, and it can activate PGC-1α and the following signaling pathways and then promote mitochondrial biogenesis. To determine the causality of PGC-1α in modulation of VEGF on this experimental paradigm, we tested the effects of resveratrol, as a positive control, and siRNA against pgc-1α, as a negative control, on VEGF expression in the hippocampus following status epilepticus.…”
Section: Resultsmentioning
confidence: 81%
“…Following status epilepticus, the mechanism of endogenous neuronal survival signals is evolutionarily conserved and may actuate extensive signaling pathways to offer the neuroprotective effect which therefore may be strong candidates for therapeutic strategies [ 39 , 42 ]. In our previous studies, both in human epilepsy [ 43 ] and animal studies following status epilepticus [ 5 , 26 , 41 , 44 , 45 , 46 ], several endogenous neuroprotective mechanisms to lessen neuronal damage were proposed, including PPARγ [ 41 ], mitochondrial uncoupling protein 2 (UCP2) [ 41 ], heat shock protein 70 [ 43 , 44 ], brain-derived neurotrophic factor [ 45 ], mitochondrial dynamin-related protein 1 [ 46 ], PGC1-α [ 5 , 26 ], and sirtuin 1 [ 5 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, Slc27a1 and Prdm16 are both putative target genes of NRF1 according to ChIP-seq results in the ENCODE Transcription Factor Targets data set [49,50]. Moreover, RSV [51][52][53] and NR [54] both have been shown to induce NRF1 expression in experimental models as part of their stimulatory effects on mitochondrogenesis mediated by the activation of the SIRT1-PGC1α axis. Altogether, it is suggested that NRF1 may play a role in linking the observed effects of the neonatal treatments applied to methylation and transcription of both studied genes.…”
Section: Discussionmentioning
confidence: 99%